“Patrones clínicos de personalidad y continuidad en el proceso de recuperación del alcoholismo en grupos de apoyo A.A tradicionales de la ciudad de Riobamba, periodo diciembre 2015 – mayo 2016”. - Pusay Villarroel, Noemí Carina (2017)
"Clinical patterns of personality and continuity in the process of recovery of alcoholism in adopting groups A.A Traditional of the city of Riobamba, period December 2015 - May 2016". ABSTRACT: The objective of this study is to analyze the influence of clinical personality patterns and the persistence in the recovery process in the traditional AA groups of Riobamba city, period December 2015 – May 2016. The present research was carried out with the participation of members of the Traditional Alcoholic Anonymous Groups in the process of recovery, the group is formed by people between 25 and 60 years of age who attend three days in a week to these centers in Riobamba city. The investigation was developed using scientific, psychometric methods, Inductive-deductive, of quantity and non-experimental design, the type of research is field, with a transversal cross and this systematic study is documentary, descriptive. It was applied as techniques and instruments of analysis a log of attendance which objective was to gather information about attendances that the members have had in the processes of recuperation, the results obtained allow establish that the people who less attend in an average of 5.5 days equivalent to the 20,37% compared to the average of 13.5 days equal to 50% of people who go to recovery processes. The Millon II Multiaxial Clinical Inventory was applied, which permit us to evaluate the personality patterns, as a conclusion the passive-aggressive personality predominates in 55,56% is the one that predominates in the study population. These results after being processed, analyzed and tabulated were represented by tables and graphs that contribute to the corresponding conclusions and recommendations. To sum it up a strategy of psychotherapeutic intervention for the treatment of alcoholism is proposed from the Minnesota Model, thus contribute the rate of desertion in the traditional groups of anonymous alcoholics in Riobamba city.